Pengaruh Perbandingan Daun Cemcem (Spondiaz Pinnata (L.F) Kurz) dengan Bubuk Stevia (Stevia Rebaudiana Bertoni) terhadap Karakteristik Teh Celup Herbal - Adnyani, Ida Ayu Nyoman Dewi; Puspawati, I Gusti Ayu Kadek Diah; Putra, I Gede Ari Mahendra (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPA, 2024)
Cemcem leaves ( Spondias Pinnata (L.f) Kurz) is one of the medicinal plants rich in bioactive compounds and serves as a raw material for loloh cemcem a traditional Balinese beverage. While cemcem leaves can be processed into herbal tea, they have a somewhat acidic taste, which makes them less popular among consumers. To address this, the addition of food ingredients is necessary, and one such ingredient is stevia powder. Stevia powder can impart sweetness when added to food products but in specific concentrations. The research is intended investigate the effect of the cemcem leaf-to-stevia powder ratio on the characteristics of herbal tea bags and determine the perfrom ratio for the best herbal tea characteristics. The study follows a Completely Randomized Design (CRD) with repeated treatments of cemcem leaves and stevia powder. The research data are analyzed using Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) if significant treatment effects are observed. The results indicated that the cemcem leaf-to-stevia powder ratio significantly affects ash content, moisture content, water-extractable solids, total phenols, antioxidant activity, total soluble solids (TSS), total acidity, and sensory characteristics evaluated through hedonic tests (color, taste, aroma, and overall acceptance) and scoring for color and taste. The best herbal tea is obtained with a cemcem leaf-to-stevia powder ratio of 50%:50%, resulting in characteristics such as moisture content: (6.93%), ash content (9.48%), water-extractable solids (36.18%), total phenols contect (38.66 mg GAE/g), antioxidant activity (88.53%), total soluble solids (0.20°Brix), total acidity (7.91%), yellowish-brown color, a sweet taste, aroma and overall acceptance were liked. Keywords: cemcem leaves, stevia powder, herbal teabag characteristics